The New Development Philosophy: Guiding Principles for China's Economic Growth. - Xiaorui, Wang (Science & Society, 2025)
Development remains a fundamental concern of human society, serving as the essential pathway to address a wide range of social, economic, and environmental challenges. Central to this endeavor are two core questions: What kind of development should be pursued, and how should it be realized? In response, the Communist Party of China (CPC) has articulated the New Development Philosophy, a strategic framework structured around five key pillars: innovation, coordination, green development, openness, and shared prosperity (Xi 2017). This approach represents a contemporary reinterpretation and extension of Marxist economic theory, providing a forward-looking vision for China's modernization and sustainable economic transformation. It rejects outdated growth paradigms and instead promotes a more balanced, inclusive, and innovation-driven model of development.